ADOPSI PETANI TERHADAP BENIH UNGGUL MEKONGGA DALAM MENINGKATKAN PRODUKTIVITAS PADI SAWAH DI DESA TAWAMELEWE KECAMATAN UEPAI KABUPATEN KONAWE - Sudarma, Ketut; Arimbawa, Putu; Jayadisastra, Yoenita (Fakultas Pertanian Universitas Halu Oleo, 2023)
Increasing population growth and increasing human needs cause the need for land to also increase. A farmer is someone who operates in the agricultural sector, mainly by managing land with the aim of growing and maintaining plants such as rice, flowers, fruit, etc., with the hope of obtaining results from these plants for their own use or selling them to other people. The aim of this research is to find out the stages of adoption of superior seeds of lowland mekongga rice and what the stages of adoption of superior seeds of mekongga lowland rice are by farmers in Tawamelewe Village, Uepai District, Konawe Regency. This research was carried out from July to September 2023 in Tawamelewe Village, Uepai District, Konawe Regency. The research results show that the majority of farmers adopted superior mekongga seed innovations through five stages of adoption, namely the awareness stage, interest stage, assessment stage, trial stage and adoption stage. There is a small number of farmers who accept the innovation of superior mekongga seeds to the level of awareness and interest.